PRODUCTIVITY AND SOCIAL ECONOMIC CONDITIONS OF RUBBER SMALLHOLDER’S IN KABUPATEN BANYUASIN, SOUTH SUMATRA PROVINCE - Yusuf, Muhammad; Sulaiman, Jamalludin (Journal of Economics, Business, and Accountancy Ventura, 2012)
Rubber is one of the top foreign exchange earners in Indonesia. Seventy percent of the land in Indonesiaused for the cultivation of rubber consists of smallholding and the remaining 30 percent are large plantations.There are 34,827 rubber smallholders in the South Sumatra Province and account for 87 percent ofrubber cultivation in the province. However, they contribute only about 55 percent of the total rubber production.In contrast, large rubber plantations which account for only 13 percent of rubber cultivation contribute45 percent of the rubber production which shows that rubber plantation productivity is very low.The objective of this study is to describe the productivity and socio economic profile and the affect of socioeconomic for rubber smallholders’ productivity. The total sample used for the study was 433 respondentsconsisting of 280 poor households and 153 non poor households. Data cross tabulation was used in thisstudy. The results show the socio economic profile reflects the level of rubber farmers education plays therole in the productivity of rubber plantation, the average working hours of the poor rubber farmers foreach age group is fewer than those who are not poor families, and the factor of the duration of workinghours is certainly associated with the area of the land to be prepared.